Potentially suitable habitat prediction of Pinus massoniana Lamb. in China under climate change using Maxent model - Chi, Yi; Wang, G. Geoff; Zhu, Mengxun; Jin, Peng; Hu, Yue; Shu, Pengzhou; Wang, Zhongxu; Fan, Aifei; Qian, Penghong; Han, Yini; Jin, Songheng (Frontiers in Forests and Global Change, 2023)
Background Pinus massoniana is an important timber species with high ecological and economic value in southern China and a pioneer species for the reforestation of barren mountains. The structure and function of the existing Masson pine ecosystem have been seriously affected by worsening habitats under current climate change. Its suitable habitat is likely to change greatly in the near future. Methods To estimate the potential geographic distribution of P. massoniana and its response to climate change, the Maxent model was selected to simulate the potentially suitable habitat and corresponding changes in the distribution pattern of P. massoniana under current and future climate scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) with two periods (2050s and 2090s). Results Under current climate conditions, the total suitable habitat area of P. massoniana was 2.08 × 106 km2, including 0.76 × 106 km2 of highly suitable habitat, concentrated mainly in Jiangxi and Zhejiang, central and southeastern Hunan, northern Fujian, central and western Chongqing, southern Anhui, central and surrounding areas of Guangdong, central and eastern Guangxi, and northern Taiwan. The areas of moderately suitable habitat and poorly suitable habitat were 0.87 × 106 km2 and 0.45 × 106 km2, respectively. Temperature and precipitation appear to be the most important predictors: precipitation of the driest month (14.7–215.6 mm), minimum temperature of the coldest month (−3.5–13.8°C), annual temperature range (8.1–32.9°C), and mean temperature of the warmest quarter (23.6–34.7°C). P. massoniana are predicted to expand their potential distribution under future climate change: by the end of this century, their total suitable habitat area increased 0.26 × 106 km2 (10.61%) and 0.45 × 106 km2 (17.05%) under the most moderate (SSP1-2.6) and severe (SSP5-8.5) warming scenarios, respectively, by mainly extending northward. Conclusion Under the different future climate scenarios, the total suitable habitat area of P. massoniana increased by mainly extending northward. Overall, our study clarifies the potential habitat distribution of P. massoniana and provides a critical empirical reference for future P. massoniana conservation and planting practices.